Effect of powder characteristics and oxygen content on modifications to the microstructural topology during hot isostatic pressing of an austenitic steel. (15th June 2019) - Irukuvarghula, S.; Hassanin, H.; Cayron, C.; Aristizabal, M.; Attallah, M.M.; Preuss, M.
Abstract: The effect of powder size distribution and oxygen content on the extent of multiple twinning and spatial distribution of oxide inclusions in hot isostatic pressed (HIPed) 316L steels was investigated using powders with different characteristics. Modifications to, and differences in their microstructural topology, were tracked quantitatively by evaluating the metrics related to twin related domains (TRDs) on specimens produced by interrupting the HIPing process at various points in time. Results revealed that powder size distribution has a strong effect on the extent of multiple twinning in the fully HIPed microstructure, with specimens produced using narrow distribution showing better statistics (i.e., homogeneously recrystallized) than the ones produced using broad size distribution. The oxide inclusion density in fully HIPed microstructures increased with the amount of oxygen content in the powders while prior particle boundaries (PPBs) were only observed in the specimens that were HIPed using broad powder distribution. More importantly, results clearly revealed that the spatial distribution of the inclusions was strongly affected by the homogeneity of recrystallization. Implications of the results are further discussed in a broader context, emphasizing the importance of utilizing the occurrence of solid state phase transformations during HIPing for controlling the microstructure evolution. Graphical abstract: Image 1